Performance changes around banks mergers and acquisitions: evidence from Poland - Budny, Katarzyna; Krasodomska, Joanna; Świetla, Katarzyna (Zmiany w wynikach działalności banków jako efekt fuzji i przejęć: przykład Polski, 2019)
This study investigates the influence of M&A on the performance of banks operating in Poland. We use a sample of 14 transactions that occurred in the Polish banking sector from 2001 to 2015. Our data set includes pre and post-merger accounting information covering a period of two years before and after the merger. We follow Pilloff’s [1996] approach to determine the average performance changes measured with ROAA and ROAE. According to the research results, M&As transactions seem to affect profitability as both ROAA and ROAE means change. However, these changes do not follow the same trend. The correlations between the acquirer’s pre-merger weighted performance measured with ROAA and ROAE and merger-related changes in performance are significant and negative. The same situation is observed as regards the target pre-merger weighted performance measured with ROAE and merger-related changes in performance. The results also suggest that large acquirers are associated with less successful M&A
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 2, s. 28-45
Keywords: banks; M&A; Poland; ROAA; ROAE; banki; fuzje i przejęcia; Polska